Environmental Sanitation with the Incidence of Helmothermal Disease - B, Muslimin; Indrayadi, Indrayadi; Susanti, Rini; Fredy Saputra, M.Khalid; Yuniarti, Elsa; Haedir, Haedir; Yermi, Yermi; Islaeli, Islaeli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Environmental sanitation of an environment consisting of sewage facilities, water supply facilities, garbage disposal facilities, and wastewater disposal facilities. And the sanitation must be owned by every housing that is maintained, clean and healthy, in order to prevent environmental pollution. This study was conducted with the aim to determine the relationship between environmental sanitation and the incidence of helminthiasis in elementary school children in the Barrang Lompo island area with a sample size of 143 children aged 5-10 years. The variables in this study were fecal disposal facilities (latrines), house floors, provision of trash bins, and clean water facilities as part of environmental sanitation. The method used was observational method with cross sectional study design. The results of this study were there was no relationship between latrine ownership and helminthiasis with a value of P = 0.077 > 0.05. There is a relationship between the floor of the house and the incidence of helminthiasis where the value of P = 0.000 < 0.005. There is a relationship between clean water facilities and the incidence of helminthiasis where P value = 0.000 < 0.05. There is a relationship between waste disposal facilities and the incidence of helminthiasis where the P value = 0.000 < 0.05. The conclusion shows that there is an association between helminthiasis in children aged 5-10 years with clean water facilities, house floors, and garbage disposal.